Using the Eurotium cristatum Fungus for Preparing Fermented Herbal Teas - Elena F. Shanenko,; Olga V. Efremenkova,; Tatiana G. Mukhamedzanova,; Yu. A. Nikolaev,; Tatiana A. Efimenko,; Marina V. Gernet,; Elena N. Bilanenko,; Ivan N. Serykh,; Sergey S. Shevelev,; Byazilya F. Vasilyeva,; Alexander V. Oleskin,; Svetlana N. Filippova,; et al. (Journal of Pharmacy and Nutrition Sciences, 2020)
Background: The biological activities of dark Chinese teas are largely due to their microbial post-fermentation. Herbal teas are traditional Russian beverages that hold special value, owing to their taste and useful medicinal properties. However, no data are available in the literature on using microbial post-fermentation for enhancing their biological activity. The goal of this work was to demonstrate that the fungus Eurotium isolated from Chinese black teas can be used for the post-fermentation of herbal teas produced from bay willow and apple leaves. Methods: Eurotium cristatum was isolated from brick Chinese tea Fujan and identified using conventional methods of microbiology and molecular biology. Low molecular weight metabolites (phenols, amines, sugars, and amino acids) were determined by HPLC. E. cristatum was grown in association with the bacterium Bacillus amyloliquefaciens. Results: It was revealed to exhibit valuable biosynthetic features, such as a lack of mycotoxins, zero antimicrobial activity, and the capacity to synthesize neuroactive amines. B. amyloliquefaciens displayed a wide spectrum of antibiotic (antimicrobial and antifungal) activities that anifested themselves even with antibiotic-resistant bacteria). While growing on green unfermented tea (Camellia sp.) E. cristatum produced and modified neuroactive amines, such as dopamine, serotonin, and epinephrine. The fungus efficiently grew during the post-fermentation of herbal teas from both bay willow and apple leaves. Even though Camellia leaves substantially differed from bay willow and apple leaves in terms of phenol content, the growth of E. cristatum on Camellia was also sufficiently good. This suggests that the growth of Eurotium fungi is not influenced by the phenolic compounds. The data obtained on the composition of phenolic compounds, carbohydrates, and amino acids in the fermented plants and raw material provide evidence that the growth of the fungus proceeds depends on the hydrolysis of high molecular weight phenols and cell biopolymers in the fermented material. Conclusion: Thus, the ability of E. cristatum to grow on plant leaves of significantly different biochemical composition provides foundations for new technologies aiming to obtain post-fermented herbal teas with high biological activity that are enriched in low molecular weight compounds including biogenic amines.